3D Printing of Rat Salivary Glands: The Submandibular–Sublingual Complex. (4th July 2013) - Cecchini, M. P.; Parnigotto, M.; Merigo, F.; Marzola, P.; Daducci, A.; Tambalo, S.; Boschi, F.; Colombo, L.; Sbarbati, A.
Summary The morphology and the functionality of the murid glandular complex, composed of the submandibular and sublingual salivary glands (SSC), were the object of several studies conducted mainly using magnetic resonance imaging (MRI). Using a 4.7 T scanner and a manganese‐based contrast agent, we improved the signal‐to‐noise ratio of the SSC relating to the surrounding anatomical structures allowing to obtain high‐contrast 3D images of the SSC. In the last few years, the large development in resin melting techniques opened the way for printing 3D objects starting from a 3D stack of images. Here, we demonstrate the feasibility of the 3D printing technique of soft tissues such as the SSC in the rat with the aim to improve the visualization of the organs. This approach is useful to preserve the real in vivo morphology of the SCC in living animals avoiding the anatomical shape changes due to the lack of relationships with the surrounding organs in case of extraction. It is also harmless, repeatable and can be applied to explore volumetric changes occurring during body growth, excretory duct obstruction, tumorigenesis and regeneration processes. 3D printing allows to obtain a solid object with the same shape of the organ of interest, which can be observed, freely rotated and manipulated. To increase the visibility of the details, it is possible to print the organs with a selected zoom factor, useful as in case of tiny organs in small mammalia. An immediate application of this technique is represented by educational classes.